Subacromial Pain Syndrome in Breast Cancer Survivors—Are Structural Shoulder Changes Verified by Ultrasound Clinically Relevant? - Ivana Klarić-Kukuz; Jure Aljinović; Blaž Barun; Marko Roki; Benjamin Benzon; Danijela Budimir Mršić; Maja Marinović Guić; Ana Poljičanin (Diagnostics)
Background/Objectives: Shoulder pain is a common treatment outcome in breast cancer survivors. While various risk factors and mechanisms for shoulder pain have been proposed, evidence is inconsistent. Increased risk of subacromial pain syndrome exists, which can lead to disability and reduced quality of life if untreated. Ultrasound is a valuable tool for detecting rotator cuff changes aiding in timely diagnosis of subacromial pain syndrome. This study aimed to assess the prevalence of rotator cuff changes to better understand chronic shoulder pain in breast cancer survivors. Methods: This cross-sectional study included 74 breast cancer survivors from the University Hospital Split. Data were collected via questionnaires and clinical interviews. Bilateral shoulder ultrasounds were performed by two blinded investigators. Categorical variables were analyzed using Chi-squared tests, and continuous variables were analyzed with T-tests or Mann–Whitney tests. Results: Pathological findings were similarly prevalent on the operated and non-operated sides (p = 0.3 and p = 0.6). Among participants with shoulder pain, ultrasound-detected pathology was present in 91% of right shoulders and 96% of left shoulders (p < 0.005). Non-painful shoulders exhibited pathology in 59% of right and 57% of left shoulders. Ipsilateral pain to the site of breast surgery was reported by 57.7% of participants, with supraspinatus pathology in 56%, acromioclavicular joint pathology in 39%, and subacromial–subdeltoid bursitis in 41%. Conclusions: Similar pathology distribution on operated and non-operated sides and frequent asymptomatic findings highlight unresolved causes of shoulder pain in breast cancer survivors. Ultrasound is valuable but requires integration with clinics for accurate diagnosis of the underlying causes of shoulder pain.